Beyond Exit Strategy: A Lifecycle Approach to CSR Sustainability and Post-Exit Engagement in a Community-Based Cooperative - Anugraheni Utami; Dyah Ayu Pujiatikinasih (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2025)
Sustainability has become a central concept in Corporate Social Responsibility (CSR) practices in Indonesia, yet existing regulatory frameworks—including the voluntary PROPER scheme and Ministerial Decree No. 1824 of 2018— have yet to provide comprehensive indicators across all stages of program planning, implementation, and evaluation, resulting in inconsistent operationalization in practice. Existing exit strategy frameworks, largely derived from international NGO contexts, inadequately capture the relational and value-creating dimensions inherent in corporate CSR This study examines CSR sustainability strategies and post-exit engagement within a corporate context, utilizing the lenses of ISO 26000, ISO 20400, and Creating Shared Value (CSV). Employing a qualitative case study design, the research focuses on Koperasi Konsumen Swadaya Pribumi Klapanunggal, an initiative by PT Solusi Bangun Indonesia. Data were gathered through participant observation, interviews with 17 informants, and document analysis, subsequently analyzed using an explanation-building approach. The findings reveal that sustainability is achieved through two key phases: the transition to independence and post-exit engagement. The independence phase emphasizes practice evaluation, institutional strengthening, and needs- based program design. Post-exit engagement is manifested through the cooperative’s integration into the company’s value chain via a local vendor policy, demonstrating the principle of CSV. Overall, this study demonstrates that CSR sustainability in community-based cooperatives extends beyond traditional exit strategies, highlighting the importance of a lifecycle approach. The proposed phase-in and phase-up mechanisms provide a practical framework for ensuring long-term, mutually beneficial outcomes between companies and local communities.